All Days 1989
DOI: 10.2118/19009-ms
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Dominated Flow in Solution Gas-Drive Reservoirs

Abstract: In this work the performance of wells in solution gas-drive reservoirs during the boundary-dominated flow period is examined. Both constant wellbore pressure and constant oil rate production modes in closed systems are considered. For the constant wellbore pressure production mode, the conditions under which procedures in the literature can be used to analyze data are discussed. Specifically, Arps's equations for performance prediction are examined and it is shown that predictions of future perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Camacho & Raghavan [2] emphasize that in many cases one single Arps curve is not sufficient to obtain a satisfactory fit, as the production data span the entire set of curves. Thus, in many situations it may be necessary to use a combination of curves to get a satisfactory fit.…”
Section: Combining Several Arps Curves To Obtain Multisegmented Produmentioning
confidence: 99%
“…Camacho & Raghavan [2] emphasize that in many cases one single Arps curve is not sufficient to obtain a satisfactory fit, as the production data span the entire set of curves. Thus, in many situations it may be necessary to use a combination of curves to get a satisfactory fit.…”
Section: Combining Several Arps Curves To Obtain Multisegmented Produmentioning
confidence: 99%
“…There have been many methods of decline curve analysis (DCA) in estimating production and reserves (Arps 1945;Fetkovich 1980;Agbi and Ng 1987;Camacho and Raghavan 1989;Palacio and Blasingame 1993;Masoner 1998;Agarwal et al 1999;Marhaendrajana and Blasingame 2001;Horne 2005, 2006). Aronofsky et al (1958) suggested an empirical model to match oil production by water injection in this type of reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this study was to conduct a comparison between the exponential model, the Li-Horne model 3 , and the harmonic model. To do so, both experimental data from core samples and production data from reservoirs with different values of permeability were analyzed using the three models.…”
Section: Introductionmentioning
confidence: 99%